Distinct anabolic signalling responses to amino acids in C2C12 skeletal muscle cells - Atherton, Philip J; Smith, Ken; Etheridge, Timothy; Rankin, Debbie; Rennie, Michael J (Amino acids, 2010)
The essential amino acids (EAA) activate anabolic signalling through mechanisms, which are unclear in detail but include increased signalling through the mammalian target of rapamycin complex 1 (mTORC1). Of all the EAA, the branched chain amino acid (BCAA) leucine has been suggested as the most potent in stimulating protein synthesis, although there have been no studies investigating the effects of each EAA on anabolic signalling pathways. We therefore undertook a systematic analysis of the effect of each EAA on mTORC1 signalling in C2C12 myotubes whereby cells were serum (4 h) and amino acid (1 h) starved before stimulation with 2 mM of each amino acid. Immunoblotting was used to detect phosphorylated forms of protein kinase B (Akt)/mTORC1 signalling enzymes. The phosphorylation of Akt was unchanged by incubation with EAA. Phosphorylation of mTOR and 4E binding protein-1 (4EBP1) were increased 1.67 ± 0.1-fold and 2.5 ± 0.1-fold, respectively, in response to leucine stimulation but not in response to any other EAA. The phosphorylation of ribosomal s6 kinase (p70S6K1) was increased by stimulation with all EAA with the exceptions of isoleucine and valine. However, the increase with leucine was significantly greater, 5.9 ± 0.3-fold compared to 1.6-2.0-fold for the non-BCAA EAA. This pattern of activation was identical in ribosomal protein s6 (RPS6) with the additional effect of leucine being 3.8 ± 0.3-fold versus 1.5-2.0-fold. Phosphorylation of eukaryotic initiation/elongation factors eIF2α and eEF2 were unaffected by EAA. We conclude that leucine is unique amongst the amino acids in its capacity to stimulate both mTOR and 4EBP1 phosphorylation and to enhance p70S6K1 signalling.